ECONOMIC ANALYSIS OF CHESTNUT HONEY PRODUCTION IN THE NATURAL CHESTNUT FORESTS OF EASTERN BLACK SEA REGION, TURKEY - N. Diktas-Bulut; İ. Daşdemir; T. Bozlar (Journal of Animal and Plant Sciences, 2022)
The present study was conducted to determine the production potential and economic significance of chestnut honey and other apiculture products in the Eastern Black Sea Region in Turkey. Although there are several studies on the production and economic aspects of flower honey in the national and international literature, the lack of adequate studies on the production and economic aspects of chestnut honey increases the significance of the present study. The study data were collected with a 19-item survey from 500 beekeepers in the Eastern Black Sea Region (Samsun, Ordu, Giresun, Trabzon, Rize, and Artvin provinces). The study data were analyzed using descriptive statistics, analysis of variance, and correlation analysis. Economic analyzes on chestnut honey production were conducted based on Gross Production Value, Net Profit, Gross Profit, and Profitability. In 2017, the profitability in chestnut honey production was calculated as 86% in the Eastern Black Sea Region. Furthermore, economic revenues in relation to honey production in chestnut forests totaled US $ 76.15 million/year in the region. The results show that chestnut honey apiculture was economically profitable in the Eastern Black Sea Region.
Keywords: Apiculture; profitability; chestnut honey economy; chestnut forests; rural development; Turkey